Improving Human Resource Quality as a Key to Harmonizing Law Enforcement in Military Judicial Environment - Prastyanto, Yanwiyatono; Saptomo, Ade (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
Law enforcement in the military justice environment in Indonesia faces unique challenges, including legal gaps and inadequate quality of human resources (HR). This impacts the effectiveness of law enforcement and justice for members of the TNI. This research aims to explore the barriers to law enforcement in military courts and provide recommendations to improve the quality of human resources and the effectiveness of law enforcement. The research method used is normative legal research with statutory and conceptual approaches. Data collection was conducted through literature study and analysis of relevant legal documents. The results showed that there were several obstacles, including the lack of clear regulations, lack of qualified human resources, and disharmony between the military and general courts. Although legal procedures exist, their implementation is often hampered by lengthy bureaucracy and a lack of training for military legal personnel. This research recommends improved education and training, competency-based recruitment, and the development of an information management system for law enforcement efficiency. To improve the effectiveness of law enforcement in military courts, structural and substantial reforms need to be carried out, including improving the quality of human resources and harmonization between the military and general justice systems. These efforts are expected to create a justice system that is more responsive and accountable to the needs of society.